Suicide and supervision: Issues for probation practice. (March 2017) - Borrill, Jo; Cook, Lisa; Beck, Amy
Suicides by offenders in the community have been relatively under-researched in comparison with prison suicides. This study examined in-depth the events and experiences of 28 service users under probation supervision, based on continuous records from the start of their sentence to their death by suicide. The study presents novel findings through mapping suicidal behaviour onto the probation supervision process, and demonstrates the complex pathways leading to suicide in this population. Key issues identified include missed appointments, the impact of legal proceedings, changes in supervision, and the importance of recording risk.